The quest for new physics with the Physics Beyond Colliders Programme - Jaeckel, Joerg; Lamont, Mike; Vallée, Claude (Nature physics, 2020)
Within the Physics Beyond Collider programme, complementary methods to high-energy frontier particle colliders to investigate the physics of elementary particles and their interactions are studied.
Gesehen am 27.04.2020